PERANAN SATUAN LALU LINTAS POLRESTA MANADO DALAM PENANGANAN MASALAH KEMACETAN LALU LINTAS - BAWENGAN, INDIRA PRISCILLA; Rorong, Arie Junus; Kolondam, Helly (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstrak:From the result of research conducted can be seen that the role of the Sat lantas Polresta Manado alreadygood enough just the problem, namely the lack of awareness of the public to be obey traffic rules despitealready given coaching, there are still many wild parking that causes congestion, public transit riders whoraise and lower the passengers place this also triggers the onset of congestion. Whereas at the time of theexecution of the operation are still many people who try to escape from being hit by a speedingticket by officersKeywords: role of Satlantas, congestion